Внутриутробное развитие желчного пузыря и внепеченочных желчных протоков у морской свинки (Cavia porcellus L.) - Круцяк, В.Н. (Вестник зоологии, 1970)
Методами гистологического и макромикроскопического исследования изучено эмбриональное развитие желчного пузыря и внепеченочных желчных протоков у 56 зародышей и 20 новорожденных морских свинок. Embryonic development of gall bladder and extrahepatic biliary ducts was studied in 56 embryos and 20 newly-born individuals of guinea pigs by the methods of histological and macromicroscopic investigation. It was established that gall bladder develops from the caudal part of liver anlage (an embryo is 7.1—7.5 mm long); muscular coat — from mesen-chyma internal layer (an embryo is 40 mm long); bladder duct develops from the narrowed part of gall bladder anlage (an embryo is 9 mm long); anlage of gall bladder glands in a form of epithelial membrane outgrowth into underlying mesenchyma occurs in embryos 40 mm long.